2016
DOI: 10.1515/popets-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Flying Eyes and Hidden Controllers: A Qualitative Study of People’s Privacy Perceptions of Civilian Drones in The US

Abstract: Drones are unmanned aircraft controlled remotely or operated autonomously. While the extant literature suggests that drones can in principle invade people’s privacy, little is known about how people actually think about drones. Drawing from a series of in-depth interviews conducted in the United States, we provide a novel and rich account of people’s privacy perceptions of drones for civilian uses both in general and under specific usage scenarios. Our informants raised both physical and information privacy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 39 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…Potentially relevant to the way dogs in public space are likely perceived as innocuous (from a privacy perspective), Wang et al [70] showed that privacy concerns regarding drone usage particularly highlight powerful yet inconspicuous data collection, as well as hidden and inaccessible drone controllers, rendering their existing privacy practices futile. Similar to drones, dogs in public space whose location is tracked could also have significant privacy implications.…”
Section: Related Work 21 Pet Wearables and Privacy Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially relevant to the way dogs in public space are likely perceived as innocuous (from a privacy perspective), Wang et al [70] showed that privacy concerns regarding drone usage particularly highlight powerful yet inconspicuous data collection, as well as hidden and inaccessible drone controllers, rendering their existing privacy practices futile. Similar to drones, dogs in public space whose location is tracked could also have significant privacy implications.…”
Section: Related Work 21 Pet Wearables and Privacy Concernsmentioning
confidence: 99%
“…Yet, they do not seem to realize that this extends to anyone interacting with their dog, nor themselves interacting with a different dog. This may be due to the novelty of these devices, and the known major concern of inconspicuous data collection when consumers are not aware of how these devices work (such as studied in drones [70]). Unlike the case of pervasive photography where younger generations have been shown to be aware of potential privacy impacts and devised 'workarounds' to prevent negative impacts [56], it seems that pervasive indirect monitoring such as in the case of pet wearables has not yet reached awareness in a large extent of the population.…”
Section: Why Should We Not Expect Consumers To Make the Leap?mentioning
confidence: 99%
“…Given the many ethical debates surrounding military drones, the use of sUAS for geospatial data collection has motivated renewed discussions of privacy issues with regard to the collection, use, and analysis of geospatial data. In a qualitative study about the privacy implications of UAS, Wang, Xia, Yao, and Huang (2016) found that territoriality (public vs. private spaces) played a key role in shaping participants' privacy concerns in relation to UAS. Unmanned systems flying within 'private spaces' (defined loosely by ownership of the space, sensitivity of the space, and activities performed within the space) were considered by respondents to be a greater invasion of privacy than those flying in 'pubic spaces'.…”
Section: Societal Implicationsmentioning
confidence: 99%
“…While it is unclear how many penalties for unsafe behaviour can be levied -these types of efforts can act as deterrents. It is important to note that these efforts are aimed at safety, rather than security or privacy concerns (see other analyses: Bracken-Roche et al, 2014;Wang et al, 2016).…”
Section: Potential Solutionsmentioning
confidence: 99%